If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(n + -3) = -2 + -9 Reorder the terms: 2(-3 + n) = -2 + -9 (-3 * 2 + n * 2) = -2 + -9 (-6 + 2n) = -2 + -9 Combine like terms: -2 + -9 = -11 -6 + 2n = -11 Solving -6 + 2n = -11 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 2n = -11 + 6 Combine like terms: -6 + 6 = 0 0 + 2n = -11 + 6 2n = -11 + 6 Combine like terms: -11 + 6 = -5 2n = -5 Divide each side by '2'. n = -2.5 Simplifying n = -2.5
| -1+4x=-77 | | 15f+6-1f=2f-6 | | 7x-1=2x-4 | | 13t-4(2t-5)=15 | | 16y^3-4y^2-2y=0 | | 2n-6*4=5 | | (3x-7)-5=12 | | 22x=35 | | 12x=37 | | 18x-32=28x/2 | | 1w+2w=24 | | -1a=9 | | 7x+4x=8 | | 7x+7-6x=6 | | 7(x-3)-2x= | | y^3-12y^2+32=0 | | -6(m+1)-2c=24 | | 2x^6-x^4-2x^2+4=0 | | 1.14x=1.25 | | x^2+4=x+4 | | 0.25x=0.275 | | -9+16x=5x+13 | | (2x-9)+3x=16 | | 30-(-2)(4-x)= | | X+19+2x=-18-2x-23 | | 4(-0.142+-0.285y)=-13 | | (x-17.5)*9.5=8.085 | | 30-(2)(4-x)= | | 13.61=142.56x^6-635.47x^5+1196.7x^4-1235.9x^3+752.4x^2-261.81x+43.991 | | (x-17.5)*9.5=1.415 | | ifx+6=3thenx | | -3.3a=-33 |